Best Practices in Operating High Frequency Metro Services - Canavan,S; Barron,A; Cohen,J; Graham,DJ; Anderson,RJ (Transportation Research Record, 2019)
© National Academy of Sciences: Transportation Research Board 2019. Most metro rail systems worldwide are facing increasing demand and the need to deliver additional capacity in key corridors. Although total capacity reflects the combination of train capacity and frequency, increasing frequency is the primary strategy to increase capacity on existing lines where infrastructure is fixed. Higher frequencies also increase efficiency, by attracting more passengers and making existing journeys faster, thereby making better use of expensive rail infrastructure and increasing both metro revenues and wider economics benefits to the cities they serve. This paper is based on a study conducted for the Community of Metros, a worldwide group of metro systems, which surveyed 17 high frequency lines. The paper first documents the characteristics of high frequency lines [with 25 trains per hour (tph) or more defined as “high frequency” and 30 tph or more as “very high frequency”] and presents the various constraints to higher frequency operations, including how they interact and the various possible solutions. Five main categories of constraints were identified, relating to signaling and train control, station and train crowding, fleet, terminal turnarounds, and service complexity. To achieve the highest frequencies, it is essential for metro systems to take a holistic approach and identify not only the immediate constraints but also secondary and tertiary constraints that may prevent the full benefits of improvements from being realized. This paper provides guidance to those operating, funding, planning, and designing metro systems in how to maximize frequency and thereby deliver greater benefits to riders, transit agencies, and stakeholders.